2014
DOI: 10.3390/su6096362
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Ecology and Environmental Lean Management: Lights and Shadows

Abstract: Current industrial production is driven by increasing globalization, which has led to a steady increase in production volumes and complexity of products aimed at the pursuit of meeting the needs of customers. In this context, one of the main tools in the management of customer value is Lean Manufacturing or Production, though it is considered primarily as a set of tools to reduce the total cost of the resources needed to achieve such needs. This philosophy has recently been enriched in the literature with case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 36 publications
(36 reference statements)
1
31
0
Order By: Relevance
“…This method allows an assessment of the sustainability of the supply chain and, at the same time, the opportunity to improve business performance The proposed integration could represent a best solution to achieve the sustainability in line with the Theory of Industrial Ecology [66]. In this context, the theory of Industrial Ecology represents a powerful analytical tool for describing the flows of material and energy that connect business and the natural world.…”
Section: Discussionmentioning
confidence: 99%
“…This method allows an assessment of the sustainability of the supply chain and, at the same time, the opportunity to improve business performance The proposed integration could represent a best solution to achieve the sustainability in line with the Theory of Industrial Ecology [66]. In this context, the theory of Industrial Ecology represents a powerful analytical tool for describing the flows of material and energy that connect business and the natural world.…”
Section: Discussionmentioning
confidence: 99%
“…Whitman et al (2008) presented the existing simulation based virtual factory and the application of modern production systems along with the integration of sustainability; Florida (1996) examined the link between advanced production & environmentally conscious manufacturing via survey, phone interviews and field research. Pauline (2009) studied the assumption that lean means green because of doing more with less, yet the evidence to support this is mostly anecdotal and the causal link is unproven; Thackeray (2008) expressed that the approach to eliminate waste, reduce cost and improve process has always been a part of what we can now call 'lean green thinking'; Rakshit and Rodrigues (2013) provided a broad perspective on combining lean with environmental sustainability to assist foundries in remaining competitive; Kyrö et al (2011) illustrated the similarities between lean & energy management and observed that the policies & practices bear a clear resemblance to lean principles ( Figure 5); Handa et al (2012) highlighted the interlinks between environmental issues & manufacturing strategies in enhancing eco-efficiency of manufacturing system and successful implementation beyond small standalone initiatives; Harrington et al (2005) investigated the factors leading to total quality environmental management driven mostly by supply-side & demand-side factors that originate internally within the firm; Dües et al (2013) explored that the implementation of green practices in turn also has a positive influence on existing lean business practices; Ioppolo et al (2014) presented the preliminary remarks for possible assessment of key factors related to their integration in envi-lean management; Jadhav et al (2013) explored green lean practices that assist in designing the structurally robust implementation strategies; Kidwell (2006) stated that environmental concerns are a part of the lean concept and air/water emission, generation of solid waste, etc. represents the waste of production; Li et al (2011) elaborated the concept of lean design, its application fields and indicated that it is the only way to establish lean enterprise that make comprehensive lean design.…”
Section: Grouping 2: Definitional Issuesmentioning
confidence: 99%
“…Concretely, the industrial ecology integrates environmental perspectives into production and consumption strategies with the consideration that environmental efficiencies, allow obtaining economic benefits [50,51]. In the industrial ecology, the dimensions presented in this paper are studied and assessed, using different instruments of analysis and decision support, such as Life Cycle Assessment (LCA), Material Flow Account (MFA), Input-Output Analysis or Exergia [52]. Water, carbon, and ecological footprint are presented in order to compare the level of sustainability and Social Life Cycle Assessment (SLCA) is strongly encouraged in urban systems; studying the level of production of the cities linked with the quality of life [53].…”
Section: Discussionmentioning
confidence: 99%